Blockchain Applied Practical Technology and Use Cases of Enterprise Blockchain for the Real World - Ashurst, Stephen; Tempesta, Stefano (New York : Productivity Press, 2021)
Blockchain is the popular name given to the exciting, evolving world of distributed ledger technology (DLT). Blockchains offer equitable and secure access to data, as well as transparency and immutability. Organisations can decide to use blockchain to upgrade whatever ledgers they are currently deploying (for example, relational databases, spreadsheets and cumbersome operating models) for their data and technology stack in terms of books and records, transactions, storage, production services and in many other areas. This book describes the applied use of blockchain technology in the enterprise world. Written by two expert practitioners in the field, the book is in two main parts: (1) an introduction to the history of, and a critical context explainer about, the emergence of blockchain written in natural language and providing a tour of the features, functionality and challenges of blockchain and DLT; and (2) a series of six applied organisational use cases in (i) trade finance, (ii) healthcare, (iii) retail savings & investments, (iv) real estate, (v) central bank digital currencies (CBDC) and (vi) fund management that offer the reader a straightforward, easy-to-read comparison between 'old world' technology (such as platforms, people and processes) versus what blockchain ledgers offer to enterprises and organisations in terms of improved efficiency, performance, security and access to business data. Blockchain is sometimes tainted by association to Bitcoin, Onecoin and others. But as cryptocurrencies and stock markets continue to rise and fall with volatility and the world economy emerges changed by coronavirus, working from home and the threat of inflation, many enterprises, organisations and governments are looking again at the powerful features of blockchain and wondering how DLT may help them adapt. This book is an ideal introduction to the practical and applied nature of blockchain and DLT solutions for business executives, business students, managers, C-suite senior leaders, software architects and policy makers and sets out, clearly and professionally, the benefits and challenges of the actual business applications of blockchain.
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Information Management